Impact of the water-curing time on the carbonation initiation period of high-volume limestone powder concrete - Radović Andrija; Carević Vedran; Marinković Snežana (Građevinski Materijali i Konstrukcije, 2025)
The high-volume limestone powder concrete (HVLPC) is one of the potential CO 2 mitigation strategies within ready-mixed concrete sector. As with other low-clinker concretes, its durability related properties, carbonation resistance especially, could present a problem in the structural applications. This work deals with the influence of the water-curing time on the carbonation initiation period of HVLPC. An experimental campaign was designed which included various curing times, from 1 day to 28 days. Beside the reference mix (ordinary Portland cement concrete - OPC), HVLPC mixes with three different percentages of limestone powder (LP) in the powder phase (47%, 58% and 65%), and with two different LP particle size distributions within each group, were designed to have similar compressive strength. All mixes were tested under accelerated and natural carbonation conditions. Test results showed significant impact of the curing time on the HVLPC carbonation resistance, but different from OPC. The Model Code 2020 prediction model was tested against test results and it was found that it largely overestimated the impact of curing duration for short curing times (1 and 3 days), while underestimated this impact for 14 and 28 days of curing. New expression for the execution transfer parameter kc was proposed based on the own experimental results.